1983
DOI: 10.1172/jci110759
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to 1,25-dihydroxyvitamin D. Association with heterogeneous defects in cultured skin fibroblasts.

Abstract: A B S T R A C T We evaluated the interaction of [3H]1,25(0H)2D3 with skin fibroblasts cultured from normal subjects or from affected members of six kindreds with rickets and resistance to 1-alpha, 25(OH)2D [1,25(OH)2D]. We analyzed two aspects of the radioligand interaction; nuclear uptake with dispersed, intact cells at 370C and binding at 0C with soluble extract ("cytosol") prepared from cells disrupted in buffer containing 300 mM KCl and 10 mM sodium molybdate.With normal fibroblasts the affinity and capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
43
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(46 citation statements)
references
References 30 publications
3
43
0
Order By: Relevance
“…A frequently associated and unexplained finding in HVDRR is total scalp and body alopecia (3), a feature said to be present in the more severely affected patients (4). Studies from a number of laboratories have revealed that the cause of the target organ resistance in HVDRR is a defect in the intracellular vitamin D receptor (VDR) (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A frequently associated and unexplained finding in HVDRR is total scalp and body alopecia (3), a feature said to be present in the more severely affected patients (4). Studies from a number of laboratories have revealed that the cause of the target organ resistance in HVDRR is a defect in the intracellular vitamin D receptor (VDR) (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
“…It was soon demonstrated that defects in the VDR were the likely cause of the HVDRR syndrome (5) and that different families exhibited different defects (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)). An additional useful finding was the demonstration that 1,25(OH)2D3 could induce the enzyme 25-hydroxyvitamin D-24-hydroxylase (24-hydroxylase) in multiple target tissues by a receptor-mediated process (27).…”
mentioning
confidence: 99%
“…As with many inborn errors of metabolism, HVDRD is a rare disorder; ∼70 kindreds have been described (3)(4)(5)(6)(7)(8)(9)(10) since the first publication almost 30 yr ago. The significance of the disease relates to its role in elucidating the physiology of vitamin D and calcium homeostasis in humans.…”
Section: Introductionmentioning
confidence: 99%
“…The term "hereditary hypocalcemic rickets resistant to calcitriol" defines more precisely this abnormality. However, based on our current knowledge of the etiology and pathophysiology of this disease, the term "hereditary vitamin D receptor defects" (HV-DRD) may be the most appropriate and precise to describe this condition.As with many inborn errors of metabolism, HVDRD is a rare disorder; ∼70 kindreds have been described (3)(4)(5)(6)(7)(8)(9)(10) since the first publication almost 30 yr ago. The significance of the disease relates to its role in elucidating the physiology of vitamin D and calcium homeostasis in humans.…”
mentioning
confidence: 99%
“…Moreover, impaired function of macrophages in vitamin D-deficient mice was corrected in vitro by 1,25-(OH)2D3 (7). The occurrence of the syndrome of end-organ resistance to 1,25-(OH)ZD~ due to defective receptors or lack of biologic response to 1,25-(OH)*D3 (8) provides an unusual opportunity of investigating the functions of 1,25-(OH)2D3 in the immune system of the human subject. Indeed, peripheral blood mononuclear cells of patients with resistance to 1,25-(OH)2D3 did not acquire receptors for 1,25-(OH)2D3 after lectin stimulation as normal mononuclear cells do.…”
mentioning
confidence: 99%